A STUDY OF URINE FROM HIV-POSITIVE AND HIV-NEGATIVE INDIVIDUALS AT ANDHRA PRADESH - Obulesu, Gundala; Ar, Hanumanthappa; E, Prabakar Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is to investigate the variations, if any, in urinary bacterial pathogens in HIV-positive and HIV-negative individuals. Methods: Urine sample, macroscopic and microscopic examination for identification of bacteria use by method of Standard loop method, using identification methods, Grams-staining, Biochemical tests. Results: Out of 75 HIV-positive males, 52 males were married, 23 males were unmarried; risk factors are sexually 28, occupationally majority were labor, 31, age group more in 19-25 age, only 9 HIV-positive patients presented with symptoms of urinary tract infection, Escherichia coli was the most frequently occurring bacterial isolate from positive urine culture followed by Klebsiella spp. Conclusion: The study period of 1 year and 8 months revealed that it is difficult to locate/identify an HIV-positive person in a place like Kadapa on account of confidentiality/lack of awareness among the population. Having identified the HIV-positive cases, collection of urine samples from the patients also needed counseling and intervention by the respective clinicians, especially when patients were not having any symptoms. Out of 50 HIV-negative individuals, only 1 (2%) urine sample is showing significant bacteriuria.